Pemberdayaan Masyarakat tentang Tuberkulosis serta Pelatihan Etika Batuk di Kelurahan Sendang Mulyo: Community Empowerment about Tuberculosis and Cough Ethics Training in Sendang Mulyo - Afriansya, Roni; Budiharjo, Teguh; Afrianti, Dina; Widodo, Widodo; Kuncara, Rachmad Bayu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Tuberculosis control requires synergy between the government and the community. The success of TB control in an area is inseparable from the role of the community, which can be pursued by empowering the community. Community empowerment in TB control is to foster awareness, ability and willingness in breaking the chain of TB transmission. This activity aims to increase the knowledge and ability of the community in breaking the chain of TB transmission. The method of activity is carried out by providing counseling and training directly to the community. The results of the activity showed an increase in knowledge and ability of the community in understanding about TB. Direct counseling on TB and direct training on how to cough properly have a good and effective impact in increasing the knowledge and abilities of the community. It is recommended that empowerment activities by providing direct material about TB and direct training on how to cough properly be carried out more intensively and also involve health cadres.